Poly[[diaqua(1,10-phenanthroline-κ2N,N′)(μ3-4-sulfonatobenzene-1,2-dicarboxylato-κ4O1:O2,O2′:O4)erbium(III)] dihydrate] - Zhang, Kou-Lin; Lin, Jian-Guo; Ng, Seik Weng (International Union of Crystallography, 2012)
The 4-sulfophthalate trianion in the polymeric complex, {[Er(C 8H 3O 7S)(C 12H 8N 2)(H 2O) 2]·2H 2O} n, bridges three water/phenanthroline-coordinated Er III ions to form a three-dimensional network architecture. The metal atom is further chelated by a carboxylate group and is covalently bonded to a monodentate carboxylate group as well as to a monodentate sulfonate group in a distorted square antiprismatic geometry. The coordinating water molecules and the lattice water molecules, one of which is disordered over two positions [major component 65 (3)%], are hydrogen bonded to the network.